Embedding Enterprise: A Business School Undergraduate Course with an Enterprise Focus. (June 2013) - Jones, Paul; Jones, Amanda; Skinner, Heather; Packham, Gary
This study profiles, through a case study of an undergraduate business programme, how a business school has embedded the theme of enterprise in its core undergraduate programme. Key participants in the development of the strategy and programme tutors and students were interviewed, to provide information for an analysis of the principle objectives and the impact of the course. The findings confirm the need to adopt a top-down strategy to identify underpinning themes that support all programme activities: the programme curriculum should focus on key themes and use innovative assessment and teaching and learning strategies, as well as added-value activities that enhance its effectiveness. The authors offer recommendations for best practice, including specific modules of study, use of guest speakers, added-value activities for developing student skills and innovative assessment strategies. It is argued that the paper will help university policy makers to construct valid programmes in which themes of enterprise and self-employment are integrated in order to enhance experiential and added-value activities.